2012
DOI: 10.18632/oncotarget.806
|View full text |Cite
|
Sign up to set email alerts
|

STAT5 triggersBCR-ABL1mutation by mediating ROS production in chronic myeloid leukaemia

Abstract: We recently reported that chronic myeloid leukaemia (CML) patients harbour high levels of STAT5 when they progress to advanced phases of disease. Advanced disease is characterized by an increased incidence of BCR-ABL1 mutations. We now describe a highly significant correlation between STAT5 expression and the incidence of BCR-ABL1 mutations in primary CML. Forced expression of STAT5 in murine BCR-ABL1 transformed cells sufficed to enhance the production of reactive oxygen species (ROS) and to trigger DNA damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 83 publications
4
63
2
1
Order By: Relevance
“…34 A recent publication described a highly significant correlation between the level of STAT5A mRNA and the occurrence of BCR-ABL1 mutations in a cohort of 50 CML patients, possibly mediated by the enforced production of reactive oxygen intermediates. 39 Further support for a link between STAT5 activity and TKI response is provided by a recent phosphoproteinprofiling study that found a significant correlation between the level of phosphorylated STAT5 and the response to TKI treatment. 40 It will be of interest to study whether and how STAT3 induces TKI resistance as STAT3 can compensate for STAT5 under certain circumstances, and there is preliminary evidence to implicate STAT3 in drug resistance in CML.…”
Section: Stat5 In Tki Resistancementioning
confidence: 97%
“…34 A recent publication described a highly significant correlation between the level of STAT5A mRNA and the occurrence of BCR-ABL1 mutations in a cohort of 50 CML patients, possibly mediated by the enforced production of reactive oxygen intermediates. 39 Further support for a link between STAT5 activity and TKI response is provided by a recent phosphoproteinprofiling study that found a significant correlation between the level of phosphorylated STAT5 and the response to TKI treatment. 40 It will be of interest to study whether and how STAT3 induces TKI resistance as STAT3 can compensate for STAT5 under certain circumstances, and there is preliminary evidence to implicate STAT3 in drug resistance in CML.…”
Section: Stat5 In Tki Resistancementioning
confidence: 97%
“…STAT5 regulates the antiapoptotic genes Bcl-xl, Bcl2 , and Mcl1 in various cell types (13)(14)(15)(16)(17). The lack of expression of these genes would explain the almost complete absence of mature NK cells in Stat5 …”
Section: Overexpression Of Bcl2 Rescues Survival Of Stat5-defi Cient mentioning
confidence: 99%
“…9 Furthermore, a recent publication described a highly significant correlation between the level of STAT5a mRNA and the occurrence of BCR-ABL1 mutations in a cohort of 50 CML patients, possibly mediated by the enforced production of reactive oxygen intermediates. 96 Moreover, using a mouse model with a conditional null mutation in the Stat5a/b gene locus, Waltz et al have determined the requirement for STAT5 in MPNs induced by BCR-ABL1 in a retroviral transplantation model of CML. 82 They provided evidence that the loss of one Stat5a/b allele results in a decrease in BCR-ABL1-induced CML-like MPN and the appearance of B-cell acute lymphoblastic leukemia, whereas complete deletion of Stat5a/b prevented the development of leukemia in primary recipients.…”
mentioning
confidence: 99%